Espectroscopia de impedância no laboratório de ensino - Chinaglia, D. L. [UNESP]; Gozzi, G. [UNESP]; Alfaro, R. A.M. [UNESP]; Hessel, R. [UNESP] (My University, 2008)
In this work we show that the configuration of an electrical circuit made up of resistors and capacitors in a black box may be determined using impedance spectroscopy, a technique that has been largely used in several scientific areas. Because the complex impedance is measured in this technique, we present basic concepts of a.c. electrical circuits analyzed with the formalism of complex numbers. The experimental setup includes a radiofrequency generator as the a.c. source for the circuit and a double-channel oscilloscope to measure both the real and imaginary parts of the complex impedance of the circuit in the black box. From the impedance spectrum we can not only determine the configuration of the electrical circuit in the black box but also the values of resistors and capacitors used. Copyright by the Sociedade Brasileira de Física. Printed in Brazil.
Impedance spectroscopy used in a teaching lab
Keywords: A.c. circuits; Black box; Complex formalism; Impedance spectroscopy